Brazil-China Relations in the 21st Century - Paulino, Luis Antonio [UNESP] (Univ Nacl La Plata, Fac Law & Science, 2020)
In 2020, Brazil celebrates 46 years of diplomatic relations with China, but the history of relations between these two countries is much older and dates back to colonial times. Official Brazil-China relations began in the late 19th century, but in the 20th century, especially after 1974, these countries resumed diplomatic relations and these relations became more robust. However, it was only in the 21st century, especially after 2003, that bilateral relations intensified, reaching their current mature level. In 2018, the election of President Jair Bolsonaro marked a new turning point in the recent history of Brazil-China relations.
Keywords: Brazil-China relations; diplomacy; trade; foreign investment